2016
DOI: 10.1038/jhg.2016.5
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of isogenic iPSCs from an individual with SCN1A mutation mosaicism as a model for investigating neurocognitive impairment in Dravet syndrome

Abstract: Dravet syndrome (DS) is a severe childhood epilepsy typically caused by de novo dominant mutations in SCN1A. Although patients with DS frequently have neurocognitive abnormalities, the precise neural mechanisms responsible for their expression have not been elucidated. There are wide phenotypic differences among individuals with SCN1A mutations, suggesting that factors other than the SCN1A mutation modify the phenotype. Therefore, a well-controlled cellular model system is required to improve our understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…This nonlinear relationship indicates that behavioral problems are not completely subject to an epileptic encephalopathy disease model, as previously suggested [19,44]. Recent research has shown that SCN1A variants could lead to changes in the dopamine system that may contribute to behavioral problems, irrespective of seizure activity [45]. This, together with the large impact of behavioral problems on HRQoL scores and the high number of families affected by it, calls for more attention regarding recognition of behavioral problems.…”
Section: Discussionmentioning
confidence: 80%
“…This nonlinear relationship indicates that behavioral problems are not completely subject to an epileptic encephalopathy disease model, as previously suggested [19,44]. Recent research has shown that SCN1A variants could lead to changes in the dopamine system that may contribute to behavioral problems, irrespective of seizure activity [45]. This, together with the large impact of behavioral problems on HRQoL scores and the high number of families affected by it, calls for more attention regarding recognition of behavioral problems.…”
Section: Discussionmentioning
confidence: 80%
“…Isogenic iPSC pairs are commonly generated by employing site‐specific nucleases for genome engineering aimed at introducing or correcting the disease mutation in an iPSC line of reference . Alternatively, a study sought to generate isogenic lines exploiting the generation of iPSCs from peripheral blood cells of the asymptomatic individual carrying a truncating SCN1A mutation in mosaicism and mother of two brothers with DS . Transgene‐free reprogramming of peripheral blood lymphocytes generated 11 iPSC clones, 2 of which harbored the SCN1A heterozygous mutation causing DS in her children, whereas the remaining clones were wild‐type.…”
Section: Modeling Scn1a Epilepsies With Ipsc Technologymentioning
confidence: 99%
“…Nevertheless, DA concentrations in media collected from neural cultures, derived from induced pluripotent stem cells from a patient with the Dravet syndrome, were higher than those from wild-type neural cultures (Maeda et al, 2016). …”
Section: Monoamines In Epilepsy: Preclinical and Clinical Evidencementioning
confidence: 99%